THE ROLE OF DIGITAL MARKETING, BRAND IMAGE, AND CUSTOMER SERVICE IN INFLUENCING PURCHASE DECISIONS AT ONE STREET FOOD IN PEKANBARU - Suyono Suyono; Enjelina Juniaty; Nyoto Nyoto; Etty Murwaningsari; Yvonne Augustin S; Muhammad Ridwan (Procuratio : Jurnal Ilmiah Manajemen, 2024)
The aim of this research is to determine the influence of digital marketing, brand image, and service quality on purchasing decisions at One Street Food in Pekanbaru. The population in this study consists of 19,000 visitors to OSF in Pekanbaru. The data analysis techniques used in this study include descriptive analysis and multiple linear regression analysis with the aid of statistical software. The population for this research consists of consumers who made purchases at One Street Food Pekanbaru. The sample size was determined using the Slovin formula, amounting to 100 people, and the sample will be taken using the accidental sampling method. The data analysis in this study employs multiple linear regression analysis with the help of SPSS. Based on the research findings, it was found that digital marketing has a positive and significant influence on purchasing decisions, brand image has a positive and significant influence on purchasing decisions, and service quality has a positive and significant influence on purchasing decisions at One Street Food in Pekanbaru. It is recommended that One Street Food (OSF) in Pekanbaru should consistently pay attention to how to create a strong brand image to foster purchasing decisions, particularly in terms of increasing the variety of tenants available for selection, so that the brand image applied to OSF can further enhance consumer purchasing decisions. Penelitian ini bertujuan untuk mengetahui pengaruh digital marketing, citra merek dan kualitas pelayanan terhadap keputusan pembelian pada One Street Food di Pekanbaru. Populasi pada penelitian ini adalah 19.000 pengujung OSF di Pekanbaru. Teknik analisis data pada penelitian ini menggunakan analisis deskriptif dan analisis regresi linier berganda dengan bantuan software statistic. Populasi penelitian ini adalah konsumen yang melakukan pembelian pada One Street Food Pekanbaru. Sedangkan jumlah sampel yang ditentukan menggunakan rumus slovin berjumlah 100 orang dan akan diambil dengan menggunakan metode accidental sampling. Analisis data dalam penelitian ini menggunakan metode analisis linear berganda dengan bantuan SPSS. Berdasarkan hasil penelitian diperoleh bahwa digital marketing berpengaruh positif dan signifikan terhadap keputusan pembelian, citra merek berpengaruh positif dan signifikan terhadap keputusan pembelian dan kualitas pelayanan berpengaruh positif dan signifikan terhadap keputusan pembelian pada One Strett Food di Pekanbaru. Disarankan kepada One Street Food (OSF) di Pekanbaru untuk diharapkan selalu memperhatikan dengan baik bagaimana cara menciptakan citra merek yang baik agar mampu menciptakan keputusan pembelian. Terutama terkait cara meningkatkan ragam tenant untuk dipilih, sehingga citra merek yang diterapkan pada OSF dapat lebih meningkatkan keputusan pembelian konsumen.